Exploring social learning practices for catchment management: a case study of two catchments in South Africa - Siyengo, Kwanele (Rhodes University, Faculty of Science, Department of Environmental Science)
Social learning is achieved through a wide range of practices and is understood in different ways through multiple definitions in the literature. It is recognised as an outcome of stakeholder engagement through collaborative activities such as catchment management. Stakeholder engagement and collaboration in catchment management helps stakeholders understand the complex systems they work in, by enabling deliberation, dialogue, knowledge sharing and interdependencies. These are seen as processes which enable not only the sustainable use of natural resources but also help to achieve outcomes of transformative social learning. In partnership with the Living Catchments Project (implemented by the South African National Biodiversity Institute - SANBI), this study explores social learning practices and facilitation "“ and the role these play for transformation. Exploring two case studies, the Olifants River catchment and the Umzimvubu River catchment, the study adopted a qualitative participatory case study approach. It used observations, semi-structured interviews and reflections to look at the social learning practices in the two catchments. Additionally, it made use of the Social Learning, Knowledge Management and Mediation (SLKMM) framework as an analytical tool to investigate social learning practices and tools in the cases and explore how support for these can be enhanced in future. The results showed that there are existing social learning platforms and facilitation practices in the two catchments. Though not often explicit, social learning exists, and various tools (analytical, visual, participatory, and conceptual) and practices can be used to facilitate social learning. The greatest challenge for transformative social learning in these catchments is the need for a monitoring and evaluation practice which documents and makes explicit important learning and transformation taking place. This is therefore why, through a set of recommendations, it is suggested that it is key to build capacities within existing facilitators and to work closely with stakeholders from research, policy, and implementation to grow the existing social learning work, for future transformation.
Keywords: Social learning; Watersheds -- South Africa; Watershed management; Natural resources Management; Olifants River Watershed (South Africa); Mzimvubu River Watershed (South Africa)